2020
DOI: 10.3390/vetsci7040151
|View full text |Cite
|
Sign up to set email alerts
|

Roughage to Concentrate Ratio and Saccharomyces cerevisiae Inclusion Could Modulate Feed Digestion and In Vitro Ruminal Fermentation

Abstract: The objective of this research was to investigate the effect of the roughage-to-concentrate (R:C) ratio and the addition of live yeast (LY) on ruminal fermentation characteristics and methane (CH4) production. The experimental design was randomly allocated according to a completely randomized design in a 4 × 4 factorial arrangement. The first factor was four rations of R:C at 80:20, 60:40, 40:60, and 20:80, and the second factor was an additional four doses of Saccharomyces cerevisiae (live yeast; LY) at 0, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 44 publications
3
27
0
2
Order By: Relevance
“…Major alterations of CH 4 in ruminants are produced through propionate fermentation, and CH 4 production decreased with yeast supplementation. This result concurred with Phesatcha et al [11] and Wang et al [34], who found that CH 4 production decreased with yeast supplementation, while Munoz et al [35] observed that DY supplementation increased CH 4 production in lactating dairy cows and Bayat et al [36] determined that yeast did not influence CH 4 emissions. Diverse effects of yeast supplementation on CH 4 synthesis were attributed to varying yeast strains, dosages, and diets utilized in the trials [28].…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4 ) Productionsupporting
confidence: 81%
See 2 more Smart Citations
“…Major alterations of CH 4 in ruminants are produced through propionate fermentation, and CH 4 production decreased with yeast supplementation. This result concurred with Phesatcha et al [11] and Wang et al [34], who found that CH 4 production decreased with yeast supplementation, while Munoz et al [35] observed that DY supplementation increased CH 4 production in lactating dairy cows and Bayat et al [36] determined that yeast did not influence CH 4 emissions. Diverse effects of yeast supplementation on CH 4 synthesis were attributed to varying yeast strains, dosages, and diets utilized in the trials [28].…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4 ) Productionsupporting
confidence: 81%
“…Ruminal pH and temperature values for all DY supplementations were reported in the optimal range by Phesatcha et al [11]. In general, rumen pH stability benefits acid-sensitive cellulolytic bacteria and is extremely beneficial to beef cattle, especially fattening cattle.…”
Section: Rumen Ecology and Blood Urea-nitrogenmentioning
confidence: 90%
See 1 more Smart Citation
“…This agrees with Cherdthong et al [40], who revealed that the addition of a high-concentrated diet supplied an enhanced proportion of C3. Furthermore, the C3 content could significantly increase when a substrate containing 80% of the concentrate was tested [35].…”
Section: Ruminal Volatile Fatty Acid (Vfa)mentioning
confidence: 99%
“…The increased fermentable substrate (sugar and starch) in the concentrate diet may have favored the growth of bacteria and protozoa, resulting in a change in the structure and diversity of microbial populations [34]. Accordingly, Phesatcha et al [35] also noticed an enhancement in the total amount of ruminal bacteria, with a comparable shift in rumen microbial population numbers in animals that were fed a high-concentrate diet versus animals that were fed a low-concentrate diet vs. those fed a low level of concentrate diet. This demonstrated that, when a rapid fermentation carbohydrate is supplied, microbial bacteria in the rumen tend to be enhanced.…”
Section: Ruminal Fermentation and Quantity Of Rumen Microorganismsmentioning
confidence: 99%